2021
DOI: 10.3390/ijerph18147594
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Long-Term Epidemic Dynamics of COVID-19 in the United States

Abstract: Coronavirus 2019 (COVID-19) is causing a severe pandemic that has resulted in millions of confirmed cases and deaths around the world. In the absence of effective drugs for treatment, non-pharmaceutical interventions are the most effective approaches to control the disease. Although some countries have the pandemic under control, all countries around the world, including the United States (US), are still in the process of controlling COVID-19, which calls for an effective epidemic model to describe the transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In spite of several studies indicate that include temperature factor in the SIR model could potentially improve the model outcomes [57], recent studies suggested that the temperature has no influence on the propagation of the COVID-19 virus [58,59]. In fact, some strains of the virus alter depending on their environments.…”
Section: -Discussionmentioning
confidence: 99%
“…In spite of several studies indicate that include temperature factor in the SIR model could potentially improve the model outcomes [57], recent studies suggested that the temperature has no influence on the propagation of the COVID-19 virus [58,59]. In fact, some strains of the virus alter depending on their environments.…”
Section: -Discussionmentioning
confidence: 99%